2016
DOI: 10.1097/01.ogx.0000481861.91828.88
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Injury at Benign Gynecologic Surgery and the Role of Cystoscopy

Abstract: Most ureteric injuries are caused by gynecologic surgery, with most occurring during procedures for benign diseases. Although such injuries are relatively rare, they are associated with significant morbidity. It is important to detect a urinary tract injury by cystoscopy intraoperatively; this allows for immediate referral and repair by a urologist during the same surgical procedure. Several medical societies have issued guidelines on the selective use of intraoperative cystoscopy. However, there are no strict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 0 publications
2
52
2
Order By: Relevance
“…Based on prior literature, bladder injury incidence was 1.75%, 0.93%, and 2.91% for abdominal, laparoscopic/robotic, and vaginal hysterectomy, respecitvely. 2,9,11 Ureteral injuries occur in 1.61%, 0.46%, and 0.46%, respecitvely. 8,9,12,13 The model's average hysterectomy costs with no cystoscopy varied from $884.89 to $1121.91.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on prior literature, bladder injury incidence was 1.75%, 0.93%, and 2.91% for abdominal, laparoscopic/robotic, and vaginal hysterectomy, respecitvely. 2,9,11 Ureteral injuries occur in 1.61%, 0.46%, and 0.46%, respecitvely. 8,9,12,13 The model's average hysterectomy costs with no cystoscopy varied from $884.89 to $1121.91.…”
Section: Resultsmentioning
confidence: 99%
“…Selectively performing cystoscopy adds between $13.20 and $26.13 to the cost of surgery, depending on the modality of hysterectomy (Table 3). With increasing risk of urinary tract injury, these costs are offset by savings that come from intraoperative, rather than delayed diagnosis, ajog.org 11 Ibeanu et al 2 Chi et al 9 Anand et al 7 Aarts et al 1 0.0046 0.0001e0.0276…”
Section: Resultsmentioning
confidence: 99%
“…In the most recent meta-analysis, Teeluckdharry et al (15) reported a lower but non-significant postoperative ureteric injury detection rates with the use of routine cystoscopy when compared to no cystoscopy (0.07% vs. 0.16%, p<0.054). The authors concluded that although this meta-analysis used a large pooled data from a total of 79 reports, most of these studies was retrospective and would thus tend to underestimate the actual injury rates.…”
Section: Discussionmentioning
confidence: 99%
“…The most common operative complication during hysterectomy or cesarean section is urinary tract injury. The exact prevalence of bladder and ureteral injury during obstetric/gynecologic surgery is unknown, though estimates range from 0.3 % to 4.3 % (Teeluckdharry et al 2015). The bladder is most commonly injured during (1) entry into the peritoneal cavity, (2) development of the bladder flap at the time of cesarean section or hysterectomy, or (3) closure of the vaginal cuff at the time of hysterectomy.…”
Section: Urinary Tract Fistulaementioning
confidence: 99%